2008
DOI: 10.1016/j.marchem.2008.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Alkyl nitrate photochemical production rates in North Pacific seawater

Abstract: Low molecular weight alkyl nitrates are produced in surface seawater from the photochemically initiated reaction of NO with organic peroxy radicals. In this study, methyl, ethyl, isopropyl, and n-propyl nitrate photochemical production rates were determined from shipboard incubation experiments. Surface water samples from a variety of different North Pacific water masses were irradiated in sunlight, with and without added nitrite. Production was observed in some, but not all unmodified waters. Production rates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 26 publications
1
40
0
Order By: Relevance
“…In our study -unlike in Neu et al (2008), which was motivated by the measurements of Blake et al (2003a) -no oceanic emissions are applied in the SH. The emission of alkyl nitrates from the ocean has been linked to both the concentration of chlorophyll and sea temperature (Chuck et al, 2002;Dahl and Saltzman, 2008). A strong seasonality exists in the chlorophyll concentrations in the SH (Myriokefalitakis et al, 2010) resulting in maximal concentrations occurring during the boreal wintertime; therefore any resulting emission flux is likely to exhibit a similar seasonality.…”
Section: Definition Of the Emission Scenarios And Sensitivity Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study -unlike in Neu et al (2008), which was motivated by the measurements of Blake et al (2003a) -no oceanic emissions are applied in the SH. The emission of alkyl nitrates from the ocean has been linked to both the concentration of chlorophyll and sea temperature (Chuck et al, 2002;Dahl and Saltzman, 2008). A strong seasonality exists in the chlorophyll concentrations in the SH (Myriokefalitakis et al, 2010) resulting in maximal concentrations occurring during the boreal wintertime; therefore any resulting emission flux is likely to exhibit a similar seasonality.…”
Section: Definition Of the Emission Scenarios And Sensitivity Studiesmentioning
confidence: 99%
“…Although a large fraction of alkyl nitrates are formed in the gas phase via Reaction (9), other direct sources are thought to exist from direct oceanic emissions (Atlas et al, 1993;Chuck et al, 2002;Dahl et al, 2005) and, to a lesser extent, biomass and savannah burning (Simpson et al, 2002). Measurements of alkyl nitrates made over the tropical ocean, along with concentration gradients of dissolved RONO 2 measured in seawater surface, infer aqueous phase production until supersaturation occurs, followed by a release into the Marine Boundary Layer (MBL), with a dependency on the dissolved nitrite concentrations (Dahl and Saltzman, 2008). Such oceanic emissions act as a direct source of additional nitrogen reservoirs into low NO x environments without the need of long-range transport.…”
Section: Introductionmentioning
confidence: 99%
“…The formation of NO • may also occur through biological activities in natural waters (Ward and Zafiriou 1988;Torrilles and Romestand 2001;Lambert et al 2007;Li et al 2008). Furthermore, photochemical formation of alkyl nitrates in surface seawater from the reaction of organic peroxy radicals with NO • has also been suggested (Dahl and Saltzman 2008;Dahl et al 2003). Once peroxynitrite is produced, it may participate in the redox chemistry of iron in natural waters through reactions with Fe III -organic complexes.…”
Section: Introductionmentioning
confidence: 99%
“…Alkyl peroxy radicals can be formed in seawater from photolysis of dissolved organic matter (DOM) and NO can be generated in seawater by the photolysis of nitrite (Blough 1997;Zafiriou and MacFarland 1981). The photochemical production of alkyl nitrates in seawater appears to be highly dependent upon the availability of NO (Dahl and Saltzman 2008;Dahl et al 2003;Moore and Blough 2002). Recent studies have also indicated that alkyl nitrate speciation depends on location and, potentially, sources of DOM (Dahl et al 2012a).…”
Section: Alkyl Nitratesmentioning
confidence: 99%